How do youth with Delayed Sleep-Wake Phase Disorder experience a chronobiological treatment protocol? An interview study - Wilhelmsen-Langeland, Ane; Dundas, Ingrid; Pallesen, Ståle; Bjorvatn, Bjørn; Nordhus, Inger Hilde; Saxvig, Ingvild West (Frontiers in Sleep, 2025)
ObjectivesTreatment with timed bright light and exogenous melatonin has been shown to effectively advance the sleep-wake rhythm in patients with Delayed Sleep-Wake Phase Disorder (DSWPD). However, the treatment protocol is demanding, which may negatively affect treatment adherence. The objective of the present study was thus to explore how young adults participating in a treatment study for DSWPD experienced the treatment protocol.MethodIndividual semi-structured interviews were conducted with 11 young adults with DSWPD. An introductory request was to rate whether they thought the treatment was worth the effort, with response options ranging from 0 to 100 (totally worth the effort). Interviews were analyzed using thematic analysis.ResultsThe mean rating of the treatment was 72.5 (range 60–100), indicating that all participants considered the benefits to outweigh the effort. The thematic analysis resulted in three themes: (1) Benefits and gains (2) Costs and losses and (3) Improving the cost-benefit ratio in order to prevail with the treatment. Participants described benefits in terms of an advanced circadian phase, improved everyday lives and self-evaluation. However, adhering to treatment and the resulting circadian phase advance also involved certain costs and losses. Still, participants also described how cost could be reduced by gradually tailoring the treatment protocol and their daily routines to individual needs.ConclusionAll participants considered the treatment to be worth the effort, but individual tailoring was necessary to minimize the effort/cost. The benefits of the treatment extended beyond sleep and circadian phase, positively affecting self-evaluation and beliefs regarding others' perception.